Arthroscopic Minced Cartilage Implantation for Chondral Lesion at the Glenoid in the Shoulder: Technical Note - Martin Bischofreiter, M.D.; Christina Hraba, M.Sc.; Franziska Lioba Breulmann, M.D.; Michael Gruber, M.D.; Michael Gattringer, M.D.; Georg Mattiassich, P.D., M.D.; Reinhold Ortmaier, M.D., Ph.D., M.Sc. (Arthroscopy Techniques)
Joint cartilage damage is a common condition, and various approaches exist to address these defects. Whenever conservative treatments have been exhausted or are inadequate, surgery should be taken into consideration. However, it is essential to consider the size of the damage as well as the subchondral bone involvement. As joint replacement is not an appropriate treatment for young people, a joint-preserving technique should be preferred. One option is minced cartilage implantation. This surgical procedure is appropriate for defects of around 2 cm2. Studies demonstrated exceptional short-term and midterm outcomes in the knee and hip. This description of technique focuses on the implementation of AutoCart augmentation on the glenoid. The purpose of this note is to gain technical evidence of an all-arthroscopic cartilage implantation technique performed within the glenoid cavity.